Consumer’s knowledge, awareness and willingness to pay for reusable face masks - Wan Hasbullah, Wan Nurul Aida Husna; Matthew, Nitanan Koshy; Hassiin, Nor Hizami (Universiti Malaysia Terengganu, 2025)
Reusable face masks are cost-effective and environmentally friendly alternatives. However, the extent to which people are aware and willing to pay for reusable face masks is unknown. Thus, the research aimed to determine the relationship between consumer knowledge and awareness and their willingness to pay (WTP) for reusable face masks, the factors influencing consumers’ WTP for reusable face masks and the average consumers’ WTP for reusable face masks in Selangor. A total of 209 respondents were chosen by convenience sampling via an online survey method. Mann-Whitney and Kruskal-Wallis analyses revealed that only the educational level was associated with a significant difference in the WTP for reusable face masks. Furthermore, the Spearman correlation analysis revealed a significant positive relationship between knowledge and awareness of reusable face masks and willingness to pay for them. Additionally, the multiple regression analysis indicated that consumer awareness significantly influenced their willingness to pay for reusable face masks. The mean maximum willingness to pay for reusable face masks in Selangor was RM12.85/USD2.92 per mask piece/person using the open-ended contingent valuation method (CVM). These findings would aid the government in developing effective strategies for promoting reusable face masks and assist manufacturers in producing reusable face masks at a price point that consumers are willing to pay, encouraging wider adoption.